Movement ecology and conservation: the case of African vultures - Faustino, Cláudia Estevinho Santos (2020)
How, why, when and where do organisms move? These questions have long been the subject of human curiosity and have motivated research such as that presented in this thesis. Movement facilitates many vital ecological processes, such as pollination or the spread of diseases. It reflects a dynamic interplay between internal (e.g., hunger, personality) and external factors (e.g., locations of key resources or predators) to the individuals. Identifying movement patterns can help researchers understand the flexibility with which animals respond to variable environmental conditions and design more effective conservation management plans. Despite the ongoing international efforts to halt biodiversity loss, many species including vultures, still face risk of extinction. Vultures are the sole obligate scavengers which play a vital role in maintaining the ecosystem balance, namely by consuming large amounts of carcasses and organic waste. Despite their ecological importance, African vultures face numerous pressures. Two of the most serious threats are food shortages caused by improved animal husbandry and over-harvesting of wild ungulate populations, and mass poisoning when they consume carcasses laced with poisons intended to kill predators of livestock. Even though the study of animal movement has a long history, these have been revolutionised by the more recent advances in tracking technology. Satellite-based electronic devices (commonly referred to as “tags”) can now be widely used to monitor the locations of wildlife. The miniaturisation of the devices, the integration of solar panels and multiple sensors and the ability to transmit data in real time have rocketed the capabilities of movement studies. The volume of data being generated is also increasing, posing greater challenges for data analysis and calling for the need to implement sophisticated statistical methods. Generalized Additive Model (GAMs) are a well-established approach to model complex structures in ecological data. GAMs are extensions of the linear model in which smooth function of an explanatory variable can be incorporated in the model structure; bivariate smooth functions can also be implemented to express interactions between two explanatory variables. These characteristics increase the model complexity as well as the computational cost, but prove extremely beneficial in describing heterogeneous patterns of the response variable appropriately. A key characteristic of geo-location movement data is that close observations (both in time and space) are likely to be correlated; this feature needs to be accounted for in order to ensure model results are reliable.An ongoing monitoring project in Namibia has been collecting information about two critically endangered vulture species. Such monitoring is generating a wealth of information that has allowed the description of movement patterns of these species in an unprecedented way. This thesis analyses those data to address existing knowledge gaps in the movement ecology of African vultures, giving special relevance to their conservation. Fifteen white-backed and two hooded vultures were equipped with satellite-based transmitters between March 2015 and November 2018, and nearly 240 thousand high resolution geo-referenced locations were analysed. The method implemented throughout this thesis adequately captured the innate autocorrelation structure of the data. Thus, the results and associated uncertainty (95% confidence intervals and coefficient of variation) are both unbiased, accurate and realistic in their associated uncertainty. This generated an unprecedented set of detailed statistically robust results on the movement ecology of the study species. An initial inspection of the animal locations analysed in this thesis revealed vultures can extend their movements through most of Namibia with some individuals also utilising its five neighbouring countries (Angola, Zambia, Zimbabwe, Botswana and South Africa). It was also found that immatures do not necessary fly farther than the adults, as suggested in the literature. Two adults and the sub-adult white-backed vultures visited locations farther than 1,000 km away from where they were first seen, up to a maximum of 1,628 km (in 188 days); these measures far exceed what has been reported. The examination of four movement metrics based on the distances and tortuosity within daily locations showed those vary in time, with no apparent pattern between individuals. The lack of an apparent pattern between birds was consistent throughout analysis, supporting individual personality plays a big role in shaping the movement of these vultures. Metrics were also interpreted jointly and this revealed some of the vultures analysed never flying to far from their central areas of activity (the locals) while others performed long exploratory flights to potentially exploit remote resources (the travellers). Preferential monthly areas were identified for each individual and both home ranges and core areas were characterised with associated uncertainty measures. Those areas showed differences both at temporal and spatial scales. Monthly home ranges were found to change dramatically through time although the respective core areas did not vary as much. There was no large variation also in the ratio of core area to home range and there was indication that vultures explore their habitat in a clearly patchy manner. As in the previous metrics, the mean range estimates were smaller for the hooded vultures when compared with the white-backed vultures. However, given the uncertainty about these estimates, no conclusive differentiation could be detected between species. The interpretation of the monthly range maps in light of the breeding season of white-backed vultures in Central Namibia generated the speculation that there may be floaters among the studied individuals. Those are nonbreeding adults known to other bird populations which perform larger movements during the breeding season. Covariates that describe habitat characteristics, climate variables, and human presence were used to assess the habitat preferences for each vulture. In keeping with previous results, each vulture showed its particular relationship with the environment. The characterisation done for each vulture detected no obvious similarities between individuals which can be of relevance in future studies that address scenarios under Climate Change. The vegetation index (NDVI), nearest distance to road and nearest distance to river were overall the most important covariates. Inside or out of protected areas was not deemed to be important for half the individuals. However, the importance of such areas was unquestionable at the individual level. Vultures utilised areas of neighbouring countries such as in the Kavango-Zambezi region supporting the importance of transboundary initiatives. This thesis presents new and meaningful insights on poorly known species of high conservation status and generated meaningful outputs that can provide the basis for tailoring future conservation plans. The findings of this comprehensive study can also be used as a baseline for future studies of detailed movement.